2012
DOI: 10.1021/ma300399c
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Critical Micelle Concentrations in Block Copolymer/Ionic Liquid Solutions: Remarkably Weak Dependence on Solvophobic Block Molecular Weight

Abstract: The effects of block copolymer molecular weight (MW) and composition on the critical micelle concentration (CMC) were studied using ionic liquids (ILs) as model solvents. Pyrene fluorescence was used to measure CMCs as a function of block MW for three polystyrene–poly(ethylene oxide) (PS–PEO) samples and three PS–poly(methyl methacrylate) (PS–PMMA) samples in 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide. The CMC decreased by a modest factor of 1.5 in the PS–PEO series, in which the solvophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 115 publications
3
27
1
3
Order By: Relevance
“…Pyrene strongly fluoresces in a non-polar environment, while in a polar environment it shows weak fluorescence intensity. This technique has been widely used to determine CMC for block copolymers and low molecular weight surfactants [13,35]. Figure 4a shows the excitation spectra of pyrene monitored at 390 nm with different concentrations of copolymer P2D2.…”
Section: Self-assembly Behavior Of Triblock Copolymersmentioning
confidence: 99%
“…Pyrene strongly fluoresces in a non-polar environment, while in a polar environment it shows weak fluorescence intensity. This technique has been widely used to determine CMC for block copolymers and low molecular weight surfactants [13,35]. Figure 4a shows the excitation spectra of pyrene monitored at 390 nm with different concentrations of copolymer P2D2.…”
Section: Self-assembly Behavior Of Triblock Copolymersmentioning
confidence: 99%
“…[43][44][45] More recently, there have been reports on more concentrated systems where it has been demonstrated that blending ILs with BCPs such as PS-b-poly(2-vinyl pyridine), [46][47][48] PS-b-poly (ethylene oxide) 49 [PEO], and PEO-b-poly(propylene oxide)-b-PEO 50 can lead to changes in morphology and d-spacing of the phase-separated domains. In this study, we blend 1-ethyl-3-methylimidazolium …”
Section: Introductionmentioning
confidence: 99%
“…For ILs with short alkyl chains, they are often used as nonaqueous solvent to construct various aggregates, including micelles [6][7][8][9][10], vesicles [8,11], microemulsions [12][13][14][15][16], and lyotropic liquid crystals (LLCs) [17]. Anderson et al investigated the micellar aggregation behavior of different surfactants in two imidazolium ILs with 1-butyl-3-methylimidazolium cation and anions of Cl À or PF À 6 (BmimCl and BmimPF 6 ) [6].…”
Section: Introductionmentioning
confidence: 99%